ANALISIS PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN SAAT PANDEMI COVID 19 (PT .TAKAGI SARI MULTI UTAMA) - Calvin Adam Koljaan; Dedi Rianto Rahadi (Universitas La Tansa Mashiro, 2021)
This study aims to determine the effect of compensation given by the company to employees during the Covid 19 pandemic. Because the effect of compensation is one of the keys to employee morale and knowing that work comfort has a very significant effect on the performance of Takagi Sari Multi company employees. This study uses online questions to employees of PT. takagi sari multi. The research method used is qualitative research methods. Based on the results of the study, it is known that compensation has a very positive effect on the comfort and pleasure of employees, especially in the conditions of the Covid 19 pandemic, compensation has a very good effect in encouraging work comfort, this factor increases employee productivity. working. Based on the study results of the company PT. Takagi Sari Multi Utama is advised to provide the best compensation in pandemic conditions, all research materials which are the result of qualitative measurements or calculations regarding certain characteristics.